Multifractal characteristics of pore structure in the terrestrial shale reservoirs of the Lianggaoshan formation in northeast sichuan basin and its geological significance - Wang, Jiping; Shao, Hongmei; Zhang, Yuanhao; Jiang, Zhenxue; Gao, Bo; Li, Lingling; Pan, Huifang; Wang, Haonan; Lu, Xi; Qiu, Hengyuan; He, Xiaobiao; Zhang, Chengju (Frontiers in Earth Science, 2025)
The exploration of shale oil resources in the Lianggaoshan Formation of the Jurassic System in the Sichuan Basin has made significant progress in recent years, revealing a vast resource potential. This study focuses on the upper Lianggaoshan Formation, employing low-temperature gas adsorption, high-pressure mercury intrusion, and nuclear magnetic resonance techniques to systematically characterize the pore structure of various lithofacies shales. Furthermore, the pore structure heterogeneity and its controlling factors were investigated through the integration of multifractal theory. Result indicate that high-organic laminated felsic shale exhibit well-developed micropores with a simple and uniform pore structure, making them ideal for shale oil accumulation. Medium-organic bedded felsic shale, also exhibiting laminated and feldspathic textures, possess a more complex mesoporous structure that facilitates hydrocarbon enrichment, but their high heterogeneity presents challenges for exploration and development. Low-organic massive argillaceous siltstone with low organic content demonstrates a complex macroporous structure and high heterogeneity, potentially limiting effective hydrocarbon recovery. Lastly, the pore structure of massive fine-silt sandstone exhibits a high degree of complexity and heterogeneity, revealing the significant influence of quartz and clay mineral interactions on pore development. These findings advance the understanding of shale pore structure and its impact on hydrocarbon enrichment and recovery in the Lianggaoshan Formation, and offer valuable guidance for optimizing “sweet spot” selection. Furthermore, the methodologies and insights presented here are broadly applicable to unconventional resource exploration and development in similar geological settings globally, providing new ideas for researchers studying shale reservoir pore systems.